A third generation of radical fluorinating agents based on N-fluoro-N-arylsulfonamides. Issue 1 (December 2018) - Meyer, Daniel; Jangra, Harish; Walther, Fabian; Zipse, Hendrik; Renaud, Philippe
Abstract Radical fluorination has been known for a long time, but synthetic applications were severely limited by the hazardous nature of the first generation of reagents such as F2 and the strongly electrophilic nature of the second generation of reagents such asN -fluorobenzenesulfonimide (NFSI) and Selecfluor® . Here, we report the preparation, use and properties ofN -fluoro-N -arylsulfonamides (NFASs), a class of fluorinating reagents suitable for radical fluorination under mild conditions. Their N–F bond dissociation energies (BDE) are 30–45 kJ mol−1 lower than the N–F BDE of the reagents of the second generation. This favors clean radical fluorination processes over undesired side reactions. The utility of NFASs is demonstrated by a metal-free radical hydrofluorination of alkenes including an efficient remote C–H fluorination via a 1, 5-hydrogen atom transfer. NFASs have the potential to become the reagents of choice in many radical fluorination processes. Common radical fluorination reagents, such as Selectofluor®, are penalized by the need for metal catalysts and possible oxidation side reactions. Here, the authors reported the synthesis and application ofN -fluoro-N -arylsulfonamides (NFASs) as third generation of radical fluorinating reagents to overcome those limitations.